PENGUJIAN ANOMALI PASAR JANUARY EFFECT PADA PERUSAHAAN LQ45 DI BURSA EFEK INDONESIA - W Pradnyaparamita, Ni Made; Rahyuda, Henny (E-Jurnal Manajemen; Vol 6 No 7 (2017), 2017)
ABSTRACT This experiment aims to determine the presence of abnormal stock returns in January and the other in that LQ45 companies listed in Indonesia Stock Exchange. The test results using SPSS through t test, showed that the average abnormal stock returns were highest in January which amounted -0.02055 and lowest in other months is equal to -7.23661. The test results showed  between the two variables is -0.210 with a significance of 0.075> 0.05 means that there is no correlation anatara before and after the January Effect. An increase in abnormal stock return of 0.2102 or 0.04 as a result of the January effect phenomenon. Abnormal Return on average before and after the January effect in the period February 2009 - January 2014 in the amount of -7.216 with a standard deviation of 14.618, t amounting to -4.454 with a significance of 0. Significance (2-tailed) showed 0.000 <0.05, there are significant differences in the abnormal stock returns in January with a month other than January of the LQ45 companies on the stock Exchange during the study period.
Keywords: return, abnormal return, January Effect